Treatment of HIV-associated facial lipoatrophy: impact on infection progression assessed by viral load and CD4 count - Flávia Machado Gonçalves Soares; Izelda Maria Carvalho Costa (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: HIV/AIDS-Associated Lipodystrophy Syndrome includes changes in body fat distribution, with or without metabolic changes. The loss of fat from the face, called facial lipoatrophy, is one of the most stigmatizing signs of the syndrome.OBJECTIVES:To evaluate the effect of FL treatment using polymethylmethacrylate (PMMA) implants on disease progression, assessed by viral load and CD4 cell count.METHODS: This was a prospective study of 44 patients treated from July 2009 to December 2010. Male and female patients, aged over 18 years, with clinically detectable FL and who had never been treated were included in the study. PMMA implantation was done to fill atrophic areas. Laboratory tests were conducted to measure viral load and CD4 count before and after treatment.RESULTS: Of the 44 patients, 72.72% were male and 27.27% female, mean age of 44.38 years. Before treatment, 82% of patients had undetectable viral load, which increased to 88.6% after treatment, but without statistical significance (p = 0.67). CD4 count before treatment ranged from 209 to 1293, averaging 493.97. After treatment, the average increased to 548.61. The increase in CD4 count after treatment was statistically significant with p = 0.02.CONCLUSION: The treatment of FL with PMMA implants showed a statistically significant increase in CD4 count after treatment, revealing the impact of FL treatment on disease progression. Viral load before and after treatment did not vary significantly.